An experimental, theoretical and kinetic modeling study of ammonia borane combustion - Jia, Mengmeng; Xie, Jiaxin; Ofei Bruce, Frederick Nii; Qin, Fei; Hu, Yiwen; Zhou, Chong Wen; Curran, Henry; Yun Hin, Taufiq Yap; Cheng, Song; Li, Yang (Elsevier, 2025)
Ammonia borane (NH3BH3) is a promising high-energy solid fuel candidate for ramjet propulsion systems. However, the detailed chemical kinetic mechanisms remain insufficiently understood. In this study, the ignition delay times (IDTs) of NH3BH3/air mixtures were experimentally investigated using a high-pressure shock tube under conditions of 5.0 and 10.0 bar over 1000 to 2300 K. A comprehensive kinetic mechanism comprising 58 species and 292 reactions was developed to describe the combustion of ammonia borane. Ab initio calculations were conducted to study hydrogen abstraction, unimolecular, and chemically activated reactions on the potential energy surfaces of NBH6 and NBH5. Geometry optimizations, vibrational frequency calculations, and dihedral angle scans were performed at the M06-2X/6-311++G(d,p) level of theory. Single-point energies (SPEs) for all species were determined using the CCSD/CBS method. The kinetic and thermochemical parameters obtained from high-level calculations were incorporated into the C3MechV3.3 framework to construct a revised mechanism. The reliability of the developed mechanism was evaluated through IDT simulations, and sensitivity and flux analyses were performed to identify the key reactions controlling the reactivity. The results indicate that the phase transition reaction NH3BH3(s) → NH3BH3 and the unimolecular decomposition reaction NH3BH3 → NH3 + BH3 play dominant roles during ammonia borane combustion.